1985
DOI: 10.1159/000138129
|View full text |Cite
|
Sign up to set email alerts
|

D-Baclofen Is an Antagonist at Baclofen Receptors Mediating Antinociception in the Spinal Cord

Abstract: The antagonistic action of D-baclofen at baclofen receptors mediating antinociception in the spinal cord was examined. Drugs were administered intrathecally to rats and effects on nociceptive threshold evaluated in the tail flick test. L-Baclofen, D-baclofen and the racemate produced dose-related increases in tail flick latency, with L-baclofen being twice as potent as the racemate and approximately 100 times more potent than D-baclofen. When D-baclofen was injected 15 min prior to L-baclofen, it produced a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…administration supports the contention that (±)-baclofen-induced antinociception is centrally mediated (Liebman & Pastor, 1980;Sawynok, 1987 reported to antagonize partially the effects of (-)-baclofen, when injected intrathecally at high doses (10pg) (Sawynok & Dickson, 1985a;Sawynok 1986 (Olpe et al, 1990). However, in our study, phaclofen injected intracerebroventricularly was unable to prevent (±)baclofen-induced antinociception.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…administration supports the contention that (±)-baclofen-induced antinociception is centrally mediated (Liebman & Pastor, 1980;Sawynok, 1987 reported to antagonize partially the effects of (-)-baclofen, when injected intrathecally at high doses (10pg) (Sawynok & Dickson, 1985a;Sawynok 1986 (Olpe et al, 1990). However, in our study, phaclofen injected intracerebroventricularly was unable to prevent (±)baclofen-induced antinociception.…”
Section: Discussionsupporting
confidence: 53%
“…Although some compounds, namely (+ )-baclofen, 6-aminovaleric acid and phaclofen have been reported to prevent (±)-baclofen-induced antinociception, their lack of brain penetration and low potency have hampered in vivo studies (Bowery, 1989). In fact, (+ )-baclofen and 6-aminovaleric acid only inhibit the antinociception if injected intrathecally at doses at least 20 times higher than those of (-)-baclofen (Sawynok & Dickson, 1985a;Sawynok, 1986).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…In the rat, intrathecal administration of baclofen increases response latencies in the tail-flick and hot-plate tests in a dose-dependent and stereospecific manner (ARAN and HAMMOND 1991;HAMMOND and DROWER 1984;SAWYNOK and DICKSON 1985;WILSON and Y AKSH 1978) and suppresses both phase 1 and phase 2 responses to injection of formalin in the hindpaw (DIRIG and Y AKSH 1995). In the rat, intrathecal administration of baclofen increases response latencies in the tail-flick and hot-plate tests in a dose-dependent and stereospecific manner (ARAN and HAMMOND 1991;HAMMOND and DROWER 1984;SAWYNOK and DICKSON 1985;WILSON and Y AKSH 1978) and suppresses both phase 1 and phase 2 responses to injection of formalin in the hindpaw (DIRIG and Y AKSH 1995).…”
Section: Studies Of Acute Nociceptionmentioning
confidence: 99%
“…In a number of behavioral studies and electrophysiological investigations in vivo, it has been shown that the (-)isomer of baclofen is more potent than the (H-)isomer [4,52,53,80,81,107] It was reported by various authors that the (-h)isomer can antagonize the actions of the (-)isomer [94,104,105] (see also Yaksh, this volume). In recent electrophysiological experiments in which intracellular recording techniques were employed however, no such antagonism could be demonstrated [4,58].…”
Section: Stereoselectivity Of Gabab Actionsmentioning
confidence: 99%